Influence of traps in gate oxide-Si film transition layers on FD MOSFET's characteristics at cryogenic emperatures - Lysenko, V.S.; Tyagulsky, I.P.; Osiyuk, I.N.; Nazarov, A.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The results of experiments on the influence of recharging the electron traps in a Si-SiO₂ transition layer on the low-temperature characteristics of fully depleted silicon in insulator MOSFET devices are presented. It is shown that the low-dose gammaradiation improves electrophysical parameters of the transition layer.